Pengaruh Penguasaan Teknologi dan Disiplin Kerja terhadap Kinerja Guru dengan Produktivitas Sebagai Variabel Intervening pada Sekolah XXX - Yani Yani; Amri Darwis; Yulina Eva Riany (Ridwan Institute, 2021)
The performance of human resources owned by the organization is a useful asset for the organization to achieve the goal. Quality and high-performance human resources are the expectations of every organization or company to improve the performance of its company. High human resource performance can benefit organizations with greaterprofitability. The purpose of this study is (1.) Analyzing the influence of technological control on productivity in xxx schools. (2.) analyze the influence of work discipline on productivity in xxx schools. (3.) analyze the influence of technological mastery on employee performance in xxx schools. (4.) analyze the effect of work discipline on employee performance in xxx school. (5.) analyze the effect of productivity on employee performance in xxx schools. The research method used is descriptive quantitative method. Descriptive methods are used to learn aspects of who, what, when and how of suatu topic. A simple descriptive concerns a univariate question or hypothesis regarding, or expresses something about, the magnitude, shape, distribution, or existence of a variable. The results showed that there is a significant and positive influence of technological mastery on employee performance. The coefficient of determination is 0.653 which means that the amount of technological mastery influence on employee performance is 65.3% and the remaining 34.7% is another factor that is not studied. There is an influence of technological mastery on productivity in xxx schools. This result explains that teachers who can master and use technology-based work equipment well will have good productivity.